Compliance to antenatal psychosocial assessment practice among midwives: a best practice implementation project. Issue 1 (18th March 2022) - Tessema, Marta; Birhanu, Dagmawit; Mizana, Biru Abdissa; Belay, Admasu; Tura, Gurmesa; Abera, Muluemebet; Birhanu, Zewdie; Feyissa, Garumma Tolu
ABSTRACT: Introduction and aims: As directed by the WHO, antenatal care providers have good opportunities to identify and refer mothers who are struggling with psychosocial problems. In Ethiopia, the pooled prevalence of perinatal depression is 25.8%, which is almost two-fold of the pooled global prevalence. Though this is an indication of the need for prompt interventions, there is no assessment targeted to this population. Therefore, the aim of this project was to promote an antenatal psychosocial assessment practice among midwives. Methods: Using the Joanna Briggs Institute Practical Application of Evidence System, 66 first visit antenatal care assessment opportunities were observed in both baseline and follow-up audit using three audit criteria. Fourteen midwives were interviewed for the first criterion. On the basis of the results, the gaps and barriers were analyzed using Getting Research into Practice strategies. Result: The baseline audit result revealed a 0% compliance rate for all evidence-based antenatal psychosocial assessment audit criteria. This scenario disclosed that there had not been psychosocial problem assessment practice at antenatal clinic. However, the postimplementation result showed that an average 91.5% practice of evidence-based antenatal psychosocial assessment was applied as per standards. Conclusion: Carrying out discussions on evidence summary with providers, on-the-job training, using local leaders' opinions, and involving relevant stakeholders appeared to be the key methods in improving compliance to best available evidence in antenatal psychosocial assessment.